Ecologie et inventaire des plantes bulbeuses au niveau de Kroumirie Nord Est Algérine - DECHIR Besma (My University, 2019)
The floristic inventory focused on the study of the ecology of bulbous plants at the Kroumirie North Eastern Algeria (case of the El Kala National Park), on thirty stations during a period stretching from 2015 to 2018. The floristic analysis was used to draw up a checklist of 67 species belonging to 36 genera and 14 families, among of which 19 species a high proportion of rare and /or endemic taxa with a percentage of 28.35% ; among them six signed taxa are endemic to algerian-tunisian (6 species): Allium duriaeanum, Bunium crassifolium, Hyacinthoides aristidis, Ophrys numida, Platanthera bifolia and Serapias stenopetala. One-third of the species surveyed is mainly represented by family of Orchidaceae, a highly diversified and dominant taxa with a rate of 31.3%. In this work, we recorded the presence of a new specie for the Algerian flora which is Ophrys fusca subsp. lupercalis. This discovery confirms that our study area is a biogeographic cross road for Mediterranean flora. Multivariate analyses revealed, on the one hand, certain environmental variables (altitude, exposition, substratum, slope, area, recovery rate of ligneous plants and recovery rate of herbaceous plants) determining the distribution of geophytes at the level of the Kroumirie North Eastern Algeria (EKNP) and on the other hand the typology of the stations. The visited sites show an alarming vulnerability and are subject to threats, particularly anthropogenic ones, for which a reflection on the protection of the habitats and their hosts appears urgent. The results obtained helped us to enrich databases on wild plants and their uses and also to better understand the phenomena encountered in forests. For this, appropriate prevention and conservation measures must be put in place to protect this exceptional biodiversity. ---------- ارتكز الجرد النباتي في هذا البحث على الدراسة البيئية للنباتات البصلية المنتشرة في المنطقة المسماة جبال الخمير بالفرنسية ‘كروميري' الواقعة شمال الشرق الجزائري (الحديقة الوطنية للقالة)، التي شملت ثلاثين محطة خلال الفترة الممتدة بين 2015 و2018. وقد نتج عن هذا الجرد الميداني إحصاء 67 نوعا نباتيا ينتمي إلى 36 جنسا و14 فصيلة نباتية، منها 19 نوعا متواجدة بنسبة عالية تضم الفئات النادرة و/أو المتوطنة بنسبة 28.35 بالمئة؛ حيث أن ستة من بين هذه الأنواع متوطنة وأصلها المنطقة الحدودية الجزائرية التونسية (6 أنواع): الثوم البري، كمون أسود اوكروية، هيسنتواد اغيستديس، وبعض السحلبيات. ثلث الأنواع النباتية التي تم حصرها وتصنيفها تنتمي إلى العائلة السحلبية، وهي الفصيلة السائدة بتنوع أجناسها حيث بلغت نسبة 31.3 بالمئة من العدد الكلي للأصناف المتواجدة في منطقة الدراسة. في هذا العمل، سجلنا وجود نوع جديد للنباتات الجزائرية المصنفة، أوفيريس فوسكا تحت نوع (لوبيركاليس). يؤكد هذا الاكتشاف أن منطقة دراستنا هي مفترق طرق جغرافي حيوي للنباتات المتوسطية. وكشفت التحليلات الإحصائية، من جهة، عن وجود متغيرات بيئية معينة ( الارتفاع ، التموقع ، الركيزة ، المنحدر، المساحة ، نسبة التغطية للنباتات الخشبية ونسبة التغطية للنباتات العشبية ) تحدد توزيع النباتات ذات أعضاء التخزين تحت الترابية على مستوى منطقة جبال الخمير (شمال شرق الجزائر)، ومن جهة أخرى، تصنيف مواقع الدراسة. وتشكل المواقع التي تمت زيارتها حالة من التقهقر تثير المخاوف، فهي عرضة للتهديدات، لا سيما تلك الناتجة من تدخل الإنسان، ولذا فإن التفكير في حماية هذه المواقع يعتبر من الأولويات. وقد أتاحت لنا النتائج إثراء قواعد البيانات المتعلقة بالنباتات البرية واستخداماتها، وفهم الظواهر التي نصادفها في الغابات فهما أفضل، وللقيام بذلك، يجب اتخاذ تدابير وقائية مناسبة لحماية هذا التنوع البيولوجي الاستثنائي. ------------------- The floristic inventory focused on the study of the ecology of bulbous plants at the Kroumirie North Eastern Algeria (case of the El Kala National Park), on thirty stations during a period stretching from 2015 to 2018. The floristic analysis was used to draw up a checklist of 67 species belonging to 36 genera and 14 families, among of which 19 species a high proportion of rare and /or endemic taxa with a percentage of 28.35% ; among them six signed taxa are endemic to algerian-tunisian (6 species): Allium duriaeanum, Bunium crassifolium, Hyacinthoides aristidis, Ophrys numida, Platanthera bifolia and Serapias stenopetala. One-third of the species surveyed is mainly represented by family of Orchidaceae, a highly diversified and dominant taxa with a rate of 31.3%. In this work, we recorded the presence of a new specie for the Algerian flora which is Ophrys fusca subsp. lupercalis. This discovery confirms that our study area is a biogeographic cross road for Mediterranean flora. Multivariate analyses revealed, on the one hand, certain environmental variables (altitude, exposition, substratum, slope, area, recovery rate of ligneous plants and recovery rate of herbaceous plants) determining the distribution of geophytes at the level of the Kroumirie North Eastern Algeria (EKNP) and on the other hand the typology of the stations. The visited sites show an alarming vulnerability and are subject to threats, particularly anthropogenic ones, for which a reflection on the protection of the habitats and their hosts appears urgent. The results obtained helped us to enrich databases on wild plants and their uses and also to better understand the phenomena encountered in forests. For this, appropriate prevention and conservation measures must be put in place to protect this exceptional biodiversity.